2014
DOI: 10.1002/eji.201344301
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and immunity to tuberculosis

Abstract: Summary The dual burden of tuberculosis and diabetes has attracted much attention in the past decade as diabetes prevalence has increased dramatically in countries already afflicted with a high burden of tuberculosis. The confluence of these two major diseases presents a serious threat to global public health; at the same time it also presents an opportunity to learn more about the key elements of human immunity to tuberculosis that may be relevant to the general population. Some effects of diabetes on innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
175
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 90 publications
8
175
0
4
Order By: Relevance
“…In contrast, CD8 ϩ T cells are generally thought to contribute to optimal immunity and protection, and a recent study demonstrated that these cells could be a better biomarker of the protective response to TB and the response to therapy than CD4 ϩ T cells (25,26). The relevance of innate cells such as monocytes/macrophages and NK cells has been well described (8). However, no studies on T-cell subpopulations, monocytes, and NK cell status have been performed in the context of RIF pharmacokinetics in TB-T2DM patients to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, CD8 ϩ T cells are generally thought to contribute to optimal immunity and protection, and a recent study demonstrated that these cells could be a better biomarker of the protective response to TB and the response to therapy than CD4 ϩ T cells (25,26). The relevance of innate cells such as monocytes/macrophages and NK cells has been well described (8). However, no studies on T-cell subpopulations, monocytes, and NK cell status have been performed in the context of RIF pharmacokinetics in TB-T2DM patients to date.…”
Section: Discussionmentioning
confidence: 99%
“…A standard low-fat diet was provided 3, 6, and 12 h after medication intake; the patients were allowed to ingest water ad libitum (17,18). After the drugs were administered, blood samples were collected 0.33, 0.66, 1, 1.5, 2, 2.5, 3,4,6,8,12, and 24 h postdose. Plasma was immediately separated and frozen at Ϫ80°C prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DM has also emerged as a common disease of the modern world so it is regarded as a potential risk factor for TB [5][6][7][8][9][10][11]. It is believed that diabetic patients have compromised immunity, which makes them more susceptible to bacterial infections such as tuberculosis [12,13]. But still the molecular link between tuberculosis and diabetes is not clearly understood [14].…”
Section: Introductionmentioning
confidence: 99%